1.4‐mJ High Energy Terahertz Radiation from Lithium Niobates. Issue 3 (15th January 2021) - Zhang, Baolong; Ma, Zhenzhe; Ma, Jinglong; Wu, Xiaojun; Ouyang, Chen; Kong, Deyin; Hong, Tianshu; Wang, Xuan; Yang, Peidi; Chen, Liming; Li, Yutong; Zhang, Jie
Abstract: Free‐space super‐strong terahertz (THz) electromagnetic fields offer multifaceted capabilities for reaching extreme nonlinear THz optics. However, the lack of powerful solid‐state THz sources with single pulse energy >1 mJ is impeding the proliferation of extreme THz applications. The fundamental challenge lies in hard to achieve high efficiency due to high intensity pumping caused crystal damage, linear absorption, and nonlinear distortion induced short effective interaction length, and so on. Here, through cryogenically cooling the crystals, tailoring the pump laser spectra, chirping the pump pulses, and magnifying the laser energies, 1.4‐mJ THz pulses are successfully realized in lithium niobates under the excitation of 214‐mJ femtosecond laser pulses via tilted pulse front technique. The 800 nm‐to‐THz energy conversion efficiency reaches 0.7%, and a free‐space THz peak electric and magnetic field reaches 6.3 MV cm −1 and 2.1 Tesla. Numerical simulations reproduce the experimental optimization processes. To show the capability of this super‐strong THz source, nonlinear absorption in high conductive silicon induced by strong THz electric field is demonstrated. Such a high‐energy THz source with a relatively low peak frequency is very appropriate not only for electron acceleration toward table‐top X‐ray sources but also for extreme THz science and nonlinear applications. Abstract : 1.4‐mJ THz pulses are successfully realized in lithium niobates via tilted pulse front technique. A free‐space THz peak electric and magnetic field reaches 6.3 MV cm −1 and 2.1 Tesla. Such a high‐energy THz source is very appropriate not only for electron acceleration toward table‐top X‐ray sources but also for extreme THz science and nonlinear applications.